Ischemic heart disease and stroke in male couriers: a cohort study using the national health insurance data and national employment insurance data - Yoon, Jiyoung; Min, Jeehee; Kim, Eun Mi; Kim, Jaiyong; Kim, Inah (Frontiers in Public Health, 2024)
Objectives This study aimed to determine the risk of ischemic heart disease (IHD) and stroke among male couriers in Korea by linking the data from the National Health Insurance (NHI) and National Employee Insurance (NEI) databases. Methods As of 2015, the NHI and NEI databases were linked using individual IDs. A cohort of male couriers, aged between 20 and 64 years, (N = 5,012) was constructed using the Korean Employment Insurance Occupational Classification (KECO-2007). For comparison, a cohort of male total wage workers (N = 5,429,176) and a cohort of office workers (N = 632,848) within the same age group were also constructed. The follow-up was conducted until 31 December 2020 to confirm the occurrence of IHD and stroke. The diagnoses were defined using the 10th revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10) codes. The criteria included medical services for more than 1 day of hospitalization or more than 2 outpatient visits. The age-standardized incidence ratio (SIR) was calculated to evaluate the risk of occurrence. The hazard ratio (HR) was calculated using the Cox model after adjusting for age, alcohol consumption, smoking, obesity, income level, and employment duration as confounding variables. Results The SIR of IHD for couriers was 1.54 (95% CI 1.31–1.78), while for office workers, it was 1.08 (95% CI 1.06–1.10), compared to male total wage workers. The SIR for stroke was higher for couriers at 1.84 (95% CI 1.40–2.28) and lower for office workers at 0.86, compared to male total wage workers. Couriers had a higher SIR for stroke at 1.84 (95% CI 1.40–2.28) and lower for office workers at 0.86 (0.83–0.89). Compared to total wage workers, couriers had a significantly higher adjusted HR for IHD at 1.60 (95% CI 1.37–1.87) and a higher HR for stroke at 1.39 (95% CI 1.07–1.79). Compared to office workers, couriers had a significantly higher HR for IHD at 1.34 (95% CI 1.13–1.59) as well as for for stroke at 1.43 (95% CI 1.08–1.88). Conclusion The incidence of IHD and stroke was higher among male couriers compared to male office workers and total wage workers, highlighting the need for implementing public health interventions to prevent IHD and stroke among couriers.